ARTIFICIAL NEURAL NETWORK FAULT MODEL STUDY - Vladimir A. Fatkhi; Daniil V. Marshakov; Vasily V. Galushka (Advanced Engineering Research, 2012)
Fault models of the artificial neural network hardware implementations are considered. The development of the neuroelement fault classes through the introduction of the additional neuron fault model class causing certain level signals appearance on their output in the interval (0,1) is offered. The experimental research of the introduced fault class impact on the artificial neural network operability is done.